Identification of a Novel Variant in MT-CO3 Causing MELAS - Xu, Manting; Kopajtich, Robert; Elstner, Matthias; Wang, Zhaoxia; Liu, Zhimei; Wang, Junling; Prokisch, Holger; Fang, Fang (Frontiers in Genetics, 2021)
Mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) is a maternally inherited mitochondrial disease. Most cases of MELAS are caused by the m.3243A>G variant in the MT-TL1 gene encoding tRNALeu(UUR). However, the genetic cause in 10% of patients with MELAS is unknown. We investigated the pathogenicity of the novel mtDNA variant m.9396G>A/MT-CO3 (p.E64K), which affects an extremely conserved amino acid in the CO3 subunit of mitochondrial respiratory chain (MRC) complex IV (CIV) in a patient with MELAS. Biochemical assays of a muscle biopsy confirmed remarkable CIV deficiency, and pathological examination showed ragged red fibers and generalized COX non-reactive muscle fibers. Transfer of the mutant mtDNA into cybrids impaired CIV assembly, followed by remarkable mitochondrial dysfunction and ROS production. Our findings highlight the pathogenicity of a novel m.9396G>A variant, and extend the spectrum of pathogenic mtDNA variants.